Penerapan Scientific Approach melalui Model Problem Based Instruction dalam Rangka Meningkatkan Hasil Belajar Matematika Siswa Kelas 6 SDS IT Karakter Anak Shalih - Haripamyu Haripamyu; Izzati Rahmi H.G; Monika Rianti Helmi; Ferra Yanuar; Hazmira Yozza; Yanita Yanita; Arrival Rince Putri; Admi Nazra; Jenizon Jenizon (Warta Pengabdian Andalas, 2021)
The learning method is given to the 6th-grade students of elementary school of SDS IT Karakter Anak Shalih still emphasizes learning by a teacher's tutoring method. Students are less interested in listening to the explanation of the subjects in a more extended period. Students cannot adequately understand the lesson's concepts explained through this lecture method. This finding is also reflected in the mid-test scores of students who still get scores below passed minimal score. The purpose of this activity was to grow and build students' ability to think critically, learn actively, and communicate learning outcomes well. In particular, the purpose of this activity was to apply a scientific approach through a problem-based instruction model in Mathematics with a lesson on Circle shape for grade 6 students. This activity was carried out in 3 stages, namely the preparation stage, starting with socialization and willingness collaboration from the elementary school, contacting the teacher to arrange a schedule of activities, and preparing for the implementation. The second stage was implementing activities, namely experimental methods, lectures, demonstrations, and small group discussions. The final stage was evaluating activities and providing input for better results. The accompaniment activities need to be continued to assist teachers in improving student learning outcomes in Mathematics.